STRUCTURAL CHARACTERIZATION OF EAST KENDENG ZONE, EAST JAVA BASIN USING 2D SEISMIC AND GRAVITY DATA - Anung Anandito, Muh
Kendeng zone is a geological region in the form of retro-arc foreland basin, influenced by plate subduction beneath Java Island in the south, volcanic activity and is well recognized by the appearance of the thrust fault series in the north. In this study, structural characterization is undertaken with the focus on the central to southern part of East Java from the Eocene to Miocene interval. The study is necessary to be conducted because knowledge about structure in the study area is currently limited due to lack of good representative data either surface data, well data or seismic data. The seismic image from the available data in the area is poor due to the thick volcanic layer at the earth surface, making subvolcanic structural imaging become difficult. The objectives of the structural characterization work are to get the possible definition of the basin geometry and structural pattern as the important component of petroleum system at the early tertiary. This research is conducted through the integration of seismic interpretation and gravity anomali inversion to get the geological model that describes the subsurface structure. Seismic interpretation provides structural map. Log density from well gives information on the density value of rock. From both, an initial density model that covers the study area is built. On the other side, gravity data is processed until Bouguer anomaly is extracted and then residual – regional effect is separated by application of spectrum analysis. Based on the evaluation and interpretation, wavenumber of 0.03 – 0.08 cycle/k is identified correspond to the Eocene structure. The estimation to the top basement depth is calculated based on the slope of power spectrum vs wavenumber and interpreted to be at 4-9 km depth. Based on the 2D seismic and gravity analysis, structural pattern is identified with E-W trending structural high, NE-SW structure being the strike slip fault and NWSE trending structural high. This geometry is then used to identify trap as one of the petroleum system components in Kendeng zone.